Metabolomic insight into the profile, in vitro bioaccessibility and bioactive properties of polyphenols and glucosinolates from four Brassicaceae microgreens - Tomas M.; Zhang L.; Zengin G.; Rocchetti G.; Capanoglu E.; Lucini L. (Elsevier BV, 2021)
In this study, four Brassicaceae microgreens species, namely kale, red cabbage, kohlrabi, and radish, were evaluated for their phytochemical compositions using spectrophotometric assays and untargeted metabolomics before and after in vitro gastrointestinal digestion. According to the in vitro spectrophotometric results, significant amounts of phenolics could be detected in each studied species, thus supporting the total antioxidant capacities recorded. Overall, metabolomics allowed annotating a total of 470 phytochemicals across the four Brassicaceae microgreens, either fresh or digested. Among polyphenols, flavonoids were the most represented class (180 compounds, including anthocyanins, flavones, flavonols, and other flavonoids), followed by phenolic acids (68 compounds, mainly hydroxycinnamic and hydroxybenzoic acids), non-flavonoid or phenolic acid-based structures (i.e., alkyl- and alkylmethoxy-phenols and tyrosol derivatives), and lignans. Also, 22 glucosinolates were annotated, including gluconapin glucoraphanin, glucobrassicin, and 4-hydroxyglucobrassicin. Noteworthy, significant differences could be observed in terms of bioaccessibility as a function of the phenolic class and the species considered. Overall, lignans exhibited the highest bioaccessibility values (14%), followed by tyrosol derivatives and flavonoids (on average, 9% and 8%, respectively). However, differences could be evidenced as a function of the species, with red cabbage having comparatively lower bioaccessibility values irrespective of the chemical class of bioactive considered. Similarly, bioaccessibility of glucosinolates significantly differed across species, ranging from 2% in kale to 43% in kohlrabi microgreens.
Keywords: In vitro antioxidant capacity; Flavonoids; Fermentation; Stability; PH; Food metabolomics; Glucosinolates; Polyphenols; Bioaccessibility; Broccoli; Brassica; Quantification; Phenolic compounds; Free rice cookies; Metabolomics; Anthocyanin; Enzyme activity; RAPHANUS-SATIVUS L.; Antioxidant activity; VITAMIN-E